Urszula Szymak, Przemysław Sianko (red.), Falconry – its influence on biodiversity and cultural heritage in Poland and cross Europe, Białystok: Ośrodek Edukacji Ekologicznej – Sokolarnia 2016, ss. 339, ISBN 978-83-87026-59-2. - Echaust, Karolina (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2019)
Recenzja książki: Urszula Szymak, Przemysław Sianko (red.), Falconry – its influence on biodiversity and cultural heritage in Poland and cross Europe, Białystok: Ośrodek Edukacji Ekologicznej – Sokolarnia 2016, ss. 339, ISBN 978-83-87026-59-2.